2017
DOI: 10.1590/s0034-759020170506
|View full text |Cite
|
Sign up to set email alerts
|

The Taste Transformation Ritual in the Specialty Coffee Market

Abstract: Although the consumer culture field has addressed the role of ritual processes in consumption, no research has yet identified how connoisseur consumers, through ritual practices, establish and manipulate their distinction from other consumers. Drawing on key concepts from ritual theory, this research addresses the role played by ritual in connoisseurship consumption and consumers' taste. In conducting an ethnographic study on connoisseurship consumption, the first author immersed himself in the North American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
23

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 47 publications
1
27
0
23
Order By: Relevance
“…There is limited research on consumer preferences for coffee’s intrinsic qualities. Preference for different intrinsic qualities depends on expertise and sensory skills of the consumer [21]. The untrained consumer has difficulties in distinguishing quality levels of coffee compared to an expert.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is limited research on consumer preferences for coffee’s intrinsic qualities. Preference for different intrinsic qualities depends on expertise and sensory skills of the consumer [21]. The untrained consumer has difficulties in distinguishing quality levels of coffee compared to an expert.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this form, consumers are willing to pay higher prices for social‐content coffees. Quintão, Brito, and Belk () found that sensory skills expertize influences preferences. Consumers with higher sensory skills tend to prefer social‐content coffees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Connoisseur consumers (CCs) are consumers that pay more attention to the goods they buy [31][32][33], such as the origin of the goods, the quality, the friendliness on the environment, and other ethnical attributes [33][34][35]. Theoretically, their behavior is relatively sustainable because they pay specific attention to the environmental issues as well as have the willingness to pay for environmentally friendly products more than general consumers [3,36,37]. They have the tendency to try understanding, evaluating, and appreciating the consumption of objects, subjectively showing a preference towards certain coffee attributes such as the origin of the coffee, the serving method, and others [9,38].…”
Section: Theoretical Frameworkmentioning
confidence: 99%